2018
DOI: 10.3889/oamjms.2018.105
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of TGF-Β1, SMAD4, SMAD7, TGFβRII and CD68-Positive TAM Densities in Papillary Thyroid Cancer

Abstract: BACKGROUND:Papillary thyroid carcinoma (PTC) accounts for 80% of the thyroid malignancies that are characterised by slow growth and an excellent prognosis. Over-expression of SMAD4 protein restores TGF-β signalling, determines a strong increase in anti-proliferative effect and reduces invasive potential of tumour cells expressing it.AIM:The study aimed to analyse the immunohistochemical expression of TGF-β1 and its downstream phosphorylated SMAD4, element and of the inhibitory SMAD7 PTC variants and their asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
(47 reference statements)
0
7
0
4
Order By: Relevance
“…Higher TAMs density was most significantly associated with lymph node metastases and with advanced tumor stage (III-IV) in PTC [25]. Other investigators had found larger PTCs had high density TAMs [4].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Higher TAMs density was most significantly associated with lymph node metastases and with advanced tumor stage (III-IV) in PTC [25]. Other investigators had found larger PTCs had high density TAMs [4].…”
Section: Discussionmentioning
confidence: 76%
“…Interleukin (IL)-17A, a signature cytokine of the T helper cell subset, Th17, has been indicated in the development of numerous inflammatory, autoimmune diseases, tumors, and in host defense against bacterial and fungal infection [16]. Besides Th17 cells, γδ T cells and macrophages are capable to produce IL-17 [21], [22], [23], [24], [25]. IL-17 can promote recruitment of macrophage and induce their cytokine/chemokine production, and thus capable of mediating a link between acquired and innate immunity, specifically, T cell and macrophage functions [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…Рак щитоподібної залози (РЩЗ) у всьому світі на сьогодні є найбільш швидко зростаючим різновидом ендокринних неоплазій, що посідає 5 місце за поширеністю серед жінок [1]. На сьогодні загально визнано, що окрім таких факторів, як стать і вік хворих, розмір та сонографічних характеристики пухлини, важливу роль у визначенні кінцевого діагнозу, прогнозування перебігу пухлинно-го процесу та тактики лікування важливу роль відіграє визначення гістологічного типу папілярного раку щитоподібної залози (ПРЩЗ) [2,7]. Незважаючи на відносно сприятливий прогноз, у багатьох випадках ПРЩЗ метастазує у реґіонарні лімфатичні вузли, що впливає на об'єм оперативного втручання, та подальшу якість життя хворих [8].…”
unclassified
“…Важливим представником пухлинного мікрооточення є макрофаги [5]. Ці клітини є джерелом широкого спектру речовин, включаючи трансформуючий фактор росту β (TGFβ), фактор некрозу пухлин α (TNF-α), інтерлейкін 10 (IL-10), фактор росту судинного ендотелію (VEGFs) тощо [7]. Ці речовини можуть впливати на розвиток та прогресування пухлин, модулюючи швидкість проліферації, міграційну активність, рівень диференціювання, ангіогенез та ін.…”
unclassified
See 1 more Smart Citation